2016
DOI: 10.1007/s12275-016-6298-y
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo efficacy of fluconazole in combination with farnesol against Candida albicans isolates using a murine vulvovaginitis model

Abstract: Farnesol is a quorum-sensing molecule that inhibits biofilm formation in Candida albicans. Previous in vitro data suggest that, in combination with certain antifungals, farnesol may have an adjuvant anti-biofilm agent. However, the in vivo efficacy of farnesol is very questionable. Therefore, the in vitro and in vivo activity of fluconazole combined with farnesol was evaluated against C. albicans biofilms using fractional inhibitory concentration index (FICI) determination, time-kill experiments and a murine v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…The MIC values for amphotericin B found in this study were much higher than those reported in various studies for Candida species [29][30][31] which may be attributable to the capacity of C. albicans to develop genetic mutations [32,33], leading to biodiversity [34].…”
Section: Discussioncontrasting
confidence: 78%
“…The MIC values for amphotericin B found in this study were much higher than those reported in various studies for Candida species [29][30][31] which may be attributable to the capacity of C. albicans to develop genetic mutations [32,33], leading to biodiversity [34].…”
Section: Discussioncontrasting
confidence: 78%
“…Strains and media. The previously well-characterized FLC-resistant and biofilm-forming C. albicans 27700 strain, isolated from a case of human vulvovaginal candidiasis, was used in the experiments (36). It was maintained on yeast extract-glucose agar slants with KH 2 PO 4 (YEGK) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…A cocktail of Candida -derived regulatory alcohols combined with nanomolar amounts of farnesol was reported to have a similar protective effect by Martins et al (2012) in their murine model of disseminated candidiasis [ 81 ]. Bozó et al (2016) did not find a farnesol-related protective effect against vaginal C. albicans infection [ 82 ], in contrast to the findings of Hisajima et al (2008) [ 80 ]. However, both administered farnesol regimens enhanced the activity of 5 mg/kg daily fluconazole treatment against fluconazole-resistant C. albicans strain [ 82 ].…”
Section: Farnesolmentioning
confidence: 97%
“…Bozó et al (2016) did not find a farnesol-related protective effect against vaginal C. albicans infection [ 82 ], in contrast to the findings of Hisajima et al (2008) [ 80 ]. However, both administered farnesol regimens enhanced the activity of 5 mg/kg daily fluconazole treatment against fluconazole-resistant C. albicans strain [ 82 ]. Similar fluconazole resistance reversion was observed in the case of planktonic cells by Jabra-Rizk et al (2006) [ 76 ] and Cordeiro et al (2013) [ 83 ].…”
Section: Farnesolmentioning
confidence: 97%